Treatment of Chronic Spontaneous Urticaria - Kaplan, Allen P. (The Korean Academy of Asthma, Allergy and Clinical Immunology; The Korean Academy of Pediatric Allergy and Respiratory Disease, 2012)
Chronic spontaneous urticaria is defined as persistent symptoms of urticaria for 6 weeks or more. It is associated with autoimmunity in approximately 45 percent of patients. Therapy is often difficult however the initial approach should employ high-dose non-sedating antihistamines; 4-6 tablets/day may be necessary. It has been shown that the response to 4 tablets/day exceeds 3, and exceeds 2, which exceeds 1. However the dose that corresponds to the maximal dose of first generation antihistamines (hydroxyzine, diphenhydramine) used previously, is 6/day. Yet over half the patients are refractory to antihistamines and other agents should be tried next. Whereas current guidelines (published) often add leukotriene antagonists and/or H(2) receptor antogonists next, these are of little utility. Likewise drugs effective for urticarial vasculitis (colchicine, dapsone, sulfasalazine, hydroxychloroquine) are effective in a small percentage of patients and no study suggests that the response rate of any of them exceeds the 30% placebo responses seen in most double-blind, placebo controlled studies. The drugs that are effective for antihistamine-resistant chronic spontaneous urticaria are corticosteroids, cyclosporine, and Omalizumab. Use of steroids is limited by toxicity. If used at all, a dose of no more than 10 mg/day should be employed with a weekly reduction of 1 mg. The response rates to cyclosporine and Omalizumab are each close to 75%. Cyclosporine can be used effectively if care is taken to monitor blood pressure, urine protein, blood urea nitrogen, and creatinine, every 6 weeks. Omalizumab has the best profile in terms of efficacy/toxicity and, once approved by federal agencies for use in chronic spontaneous urticaria, a dramatic change in the treatment paradigm, whether associated with autoimmunity or not, is predicted. A phase 3 trial is currently in place. Refractoriness to both Omalizumab and cyclosporine is expected to be less than 5 percent of patients. Other agents, can then be tried.